Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Spatiotemporal patterns of egg predation in forest islands: an experimental approach - Tellería, J L; Santos, T (Biological Conservation, 1992)
Thirty holm oak Quercus rotundifolia forests, ranging from 0·1 to 350 ha, were studied in central Spain to analyse the spatial and temporal patterns of predation in relation to size of forest patches. During two springs (1988 and 1989), quail Coturnix coturnix eggs were placed in these forests to evaluate predation rates. Two trials (April and June) during each year were performed to study the intraseasonal and interyear constancy of predation. Results showed that predation rate tends to increase with forest fragmentation, although forest size was poorly related to predation rate. Predation rates seemed to be constant within spring seasons and between years. These results suggest that predators concentrate their search activities in some selected forests, thus accentuating their effect on prey species.
Keywords: Forest patches; forest size; fragmentation (voyant); predation rates